Development of a genetic engineering toolbox for syngas-utilizing acetogen Clostridium sp. AWRP - Hae Jun Kwon; Joungmin Lee; Soo Jae Kwon; Hyun Sook Lee (Microbial Cell Factories, 2024)
Abstract Background Clostridium sp. AWRP (AWRP) is a novel acetogenic bacterium isolated under high partial pressure of carbon monoxide (CO) and can be one of promising candidates for alcohol production from carbon oxides. Compared to model strains such as C. ljungdahlii and C. autoethanogenum, however, genetic manipulation of AWRP has not been established, preventing studies on its physiological characteristics and metabolic engineering. Results We were able to demonstrate the genetic domestication of AWRP, including transformation of shuttle plasmids, promoter characterization, and genome editing. From the conjugation experiment with E. coli S17-1, among the four replicons tested (pCB102, pAMβ1, pIP404, and pIM13), three replicated in AWRP but pCB102 was the only one that could be transferred by electroporation. DNA methylation in E. coli significantly influenced transformation efficiencies in AWRP: the highest transformation efficiencies (102–103 CFU/µg) were achieved with unmethylated plasmid DNA. Determination of strengths of several clostridial promoters enabled the establishment of a CRISPR/Cas12a genome editing system based on Acidaminococcus sp. BV3L6 cas12a gene; interestingly, the commonly used CRISPR/Cas9 system did not work in AWRP, although it expressed the weakest promoter (C. acetobutylicum P ptb ) tested. This system was successfully employed for the single gene deletion (xylB and pyrE) and double deletion of two prophage gene clusters. Conclusions The presented genome editing system allowed us to achieve several genome manipulations, including double deletion of two large prophage groups. The genetic toolbox developed in this study will offer a chance for deeper studies on Clostridium sp. AWRP for syngas fermentation and carbon dioxide (CO2) sequestration.